UPAYA PENINGKATAN MUTU PENDIDIKAN AGAMA DI MADRASAH IBTIDAIYAH (SUATU KAJIAN TEORITIS-EMPIRIS) - Sjakir Lobud (Hunafa: Jurnal Studia Islamika, 2007)
Religious education plays a remarkable role for  developing humans’ morality. Therefore, in the National Development  of Indonesia, religious education posses a chief position. This important position is implemented in schools throughout Indonesia, from elementary level to university level , both schools based on religious teaching and those based on secular one. For instance, at the elementary religious school, religious education has become one of  nationally-tested subject. However,  Islamic education at this level of education is considered to be abortive since pupils of this school  are still unable to practice their religious teaching in their daily life. Based on this, efforts to enhance the quality of religious education at this  basic level of education must be made. What kinds of efforts should be made for that purpose, will be elaborated in this artikel.                Kata Kunci:  Mutu pendidikan agama, Madrasah Ibtidaiyah